The Correlation between Critical Thinking Skills and Argumentative Writing Skills in Moroccan Higher Education : The Case of the Faculty of Languages, Letters and Arts Ibn Tofail Universty, Kenitra - Beniche, Mounir (International Journal of Language and Literary Studies, 2023)
The aim of this study is to examine the correlation between two major variables which are critical thinking skills and argumentative writing skills in Moroccan higher education. The participants were Semester 4 and Semester 6 students (English department, Faculty of Languages, Letters and Arts Ibn Tofail Universty, Kenitra). 100 students participated in the study. 50 students from semester 4 and 50 students from semester 6. The study resorted to the correlation design for measuring the degree of association between two variables adopting the statistical method of correlation analysis. Hence , a critical thinking test (AssessmentDay Practice Test Experts, 2018) was displayed to test students’ critical thinking skills. Then, the students were asked to write an argumentative essay about social media and everday communication . For the analysis of the collected data, the study used SPSS software (Statistical Package for the Social Sciences, version 23). Pearson’s correlation coefficient was applied to examine the significant relationship between critical thinking skills and argumentative writing. The study result showed that correlation coefficient of critical thinking test and argumentative essay of S4 students is 0. 683 and of of S6 is 0. 781 which implies that the two tests are positively correlated and the correlation between critical thinking and argumentative writing is positive and very significant.